Revision of the South Pacific endemic genera Orthopsyche McFarlane 1976, Abacaria Mosely 1941 and Caledopsyche Kimmins 1953 with the description of 29 new species (Trichoptera: Hydropsychidae) - Oláh, János; Johanson, Kjell Arne; Barnard, Peter C. (Zootaxa, 2006)
The taxonomy of the SE Pacific endemic genera Orthopsyche McFarlane 1976, Abacaria Mosely 1941, and Caledopsyche Kimmins 1953 is revised, and 29 species are described as new. Orthopsyche is divided into 6 species groups. The Orthopsyche fimbriata group contains the 4 species: O. fimbriata (McLachlan), O. thomasi (Wise), O. amiena (Sykora), n. comb., and O. wardi Oláh & Johanson, n. sp. The O. tneda group includes the 2 species: O. tneda Oláh & Johanson, n. sp. and O. rashala Oláh & Johanson, n. sp. The Orthopsyche peta group holds the 5 species O. peta Oláh & Johanson, n. sp., O. piuna Oláh & Johanson, n. sp., O. mcfarlanei Oláh & Johanson, n. sp., O. ayapona Oláh & Johanson, n. sp., and O. schefterae Oláh & Johanson, n. sp. The largest Orthopsyche nadauna group includes 6 species: O. pakaha Oláh & Johanson, n. sp., O. nadauna Oláh & Johanson, n. sp., O. vrupama Oláh & Johanson, n. sp., O. sematho Oláh & Johanson, n. sp., O. neboissi Oláh & Johanson, n. sp., and O. imbah Oláh & Johanson, n. sp. The Orthopsyche kina group holds 2 species: O. kina Oláh & Johanson, n. sp. and O. edhamasa Oláh & Johanson, n. sp. The Orthopsyche touna group is monotypic, with only O. touna Oláh & Johanson, n. sp. represented.      Abacaria is divided into 6 species groups, with one incertae sedis. The Abacaria subfusca group includes the 3 species A. subfusca Kimmins, A. orkeni Illies, and A. beroni, n.comb. The Abacaria ruficeps group holds 3 species: A. ruficeps (Brauer), A. robinsoni Oláh & Barnard, n. sp., and A. moselyi Oláh & Barnard, n. sp. The Abacaria nuhu group includes the 2 species: A. nuhu Oláh & Barnard, n. sp. and A. cristova Oláh & Barnard, n. sp. The Abacaria fijiana group comprises the 3 species A. fijiana (Mosely), A. wekana Oláh & Barnard, n. sp., and A. levu Oláh & Barnard, n. sp. The Abacaria kosova group includes the 2 species A. kosova Oláh & Barnard, n. sp. and A. savura Oláh & Barnard, n. sp. A single species from New Caledonia, A. caledona Oláh & Johanson, n. sp. belongs to the Abacaria caledona group. A. picea (Brauer) is incertae sedis within Abacaria.        Caledopsyche is divided into 3 species groups, the Caledopsyche kimminsi group with the 6 species C. kimminsi Oláh & Johanson, n. sp., C. noumea Oláh & Johanson, n. sp., C. leander Schefter & Ward, C. cerberus Schefter & Ward, C. cheesmanae Kimmins, and C. phallaina Schefter & Ward. The Caledopsyche erotos group includes the single species C. erotos Schefter & Ward. The Caledopsyche atalanta group holds the 2 species C. atalanta Schefter & Ward, and C. apide Oláh & Johanson, n. sp.